Benefit of biologics initiation in moderate versus severe rheumatoid arthritis: evidence from a United States registry. (8th March 2017) - Kavanaugh, Arthur; Keystone, Edward; Greenberg, Jeffrey D.; Reed, George W.; Griffith, Jenny M.; Friedman, Alan W.; Saunders, Katherine C.; Ganguli, Arijit
Abstract: Objectives. To compare clinical outcomes and treatment patterns among patients with moderate vs severe RA following biologic DMARD initiation. Methods. Biologics-naive patients with moderate to severe RA [Clinical Disease Activity Index (CDAI) >10] who initiated a biologic DMARD were selected from the Corrona registry (2001–13). CDAI, functional status [modified HAQ (mHAQ)] and patterns of drug use were compared at 1 and 2 years post-initiation between patients with moderate (CDAI >10⩽22) vs severe (CDAI >22) baseline disease activity. Results. A total of 1596 patients (817 severe, 779 moderate) had ⩾1 year of follow-up and 1269 (635 severe, 634 moderate) had ⩾2 years of follow-up. Patients with severe vs moderate baseline disease activity experienced greater improvements in disease activity [mean change in CDAI −18.9 vs −6.0 at year 1; −21.0 vs −7.1 at year 2 ( P < 0.0001)] and physical function [mean change in mHAQ −0.2 vs −0.1 ( P < 0.0001) at year 1; −0.2 vs −0.1 ( P = 0.0013) at year 2]. Greater proportions of patients with moderate vs severe disease activity achieved remission (CDAI ⩽2.8) [22.7 vs 15.8% ( P = 0.0003) at year 1; 25.9 vs 20.9% ( P = 0.0396) at year 2] or low disease activity (CDAI <10) [60.1 vs 41.2% at year 1; 66.7 vs 49.4% at year 2 ( P < 0.0001)]. Most patients remained on the original biologic drug (>70% at year 1; >62% at year 2). Conclusion. With biologic therapy, RA patients with higher baseline disease activity achieved greater improvements in measures of disease activity than those with lower levels of disease, but less often achieved the common targets of remission or low disease activity.